PARADIGMATIC APPROACH TO SYSTEM MANAGEMENT IN THE HOSPITALITY INDUSTRY - MIZYUK, B.; MELNYK, IRYNA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Building a modern competitive economy requires intensification of management and investment activities on the basis of innovation. In the conditions of intensification of the process of Ukraine’s integration into the European community there is a need to change the guidelines and transformational factors of the hospitality industry. The manifestation of crisis trends in the field of tourism and hotel and restaurant business indicates the need for a systematic approach to the organization and regulation of this area. The problem of revising the old and creating a new system management paradigm in the hospitality industry comes to the fore. The development of management, as art and theory, has evolved. However, the change in management tasks at certain stages of development of economic relations indicates a change in perceptions and approaches to the organization and regulation of economic and production processes. Moreover, this is determined by the dynamics of change in all areas and spheres of socio-economic, cultural, health and other forms of social activity. Depending on their importance, views on management changed at different stages, which manifested itself in the formation of relevant conceptual positions and different management paradigms and was reflected in the emergence of different scientific schools, such as "scientific management", "classical", "human relations", "quantitative approach”, “behavioral sciences”, “production activities”, etc. Features of the current stage of development of public relations, the need for a strategic vision of the prospects of technological innovation necessitate a new approach to management, substantiation of new theoretical and practical principles of technological modernization of management systems in all sectors of the hospitality industry. The article deals with the pragmatic direction of creating tools for system management of the hospitality industry, in particular the transition to a new system of views on the activities of enterprises from the standpoint of theoretical positions in systems’ theory, organizational theory, systematic and situational approaches and analysis, economic theory, social psychology, computer sciences, and computer technologies. The new model of system management involves the connection and consistent use of theoretical principles and tools for the functioning of the control system. It is established that the system management paradigm is a process of regulation and coordination of production and economic operations, which is based on the properties of the process as a complex system; subordination to the laws of the organizational theory; the availability of tools that would ensure the manifestation of the properties of the system and the implementation of the laws of organizational theory.